2008
DOI: 10.1152/jn.00598.2007
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL Inhibitor ABT-737 Reveals a Dual Role for Bcl-xL in Synaptic Transmission

Abstract: A role for BCL-xL in regulating neuronal activity is suggested by its dramatic effects on synaptic function and mitochondrial channel activity. When recombinant BCL-xL is injected into the giant presynaptic terminal of squid stellate ganglion or applied directly to mitochondrial outer membranes within the living terminal, it potentiates synaptic transmission acutely, and it produces mitochondrial channel activity. The squid, however, is a genetically intractable model, making it difficult to apply genetic tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 49 publications
2
55
1
Order By: Relevance
“…The neurologic toxicity was expected based on preclinical toxicology experiments and was decreased by prolonging the rate of infusion. A recent report implicates Bcl-xl in synaptic function with disruption induced in vitro by the Bcl-2/Bclxl/Bcl-w antagonist ABT-737, 13 thus supporting the conclusion that the CNS effects of obatoclax, which is known to cross the blood brain barrier, represent an on-target effect. Monitoring of peripheral blood counts throughout the study revealed occasional episodes of grade 3 or 4 neutropenia and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 68%
“…The neurologic toxicity was expected based on preclinical toxicology experiments and was decreased by prolonging the rate of infusion. A recent report implicates Bcl-xl in synaptic function with disruption induced in vitro by the Bcl-2/Bclxl/Bcl-w antagonist ABT-737, 13 thus supporting the conclusion that the CNS effects of obatoclax, which is known to cross the blood brain barrier, represent an on-target effect. Monitoring of peripheral blood counts throughout the study revealed occasional episodes of grade 3 or 4 neutropenia and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 68%
“…Remarkably, the protective effect of ischemic preconditioning in this experimental paradigm occurs despite caspase-3 activation (Miyawaki et al, 2008). Emerging studies suggest that, beyond apoptosis, regulated interaction of BAD and BAD-like ligands and BCL-X L in neurons may further influence cellular bioenergetics and determine the ATP levels available for synapse formation or recovery after ischemic insult (Hickman et al, 2008). Specifically, the interaction of BAD and BCL-X L may affect the refilling of synaptic vesicles and trafficking of mitochondria to synaptic termini for efficient neurotransmission (Jonas et al, 2003;Li et al, 2008).…”
Section: Bad: a Sentinel For Select Apoptotic Signalsmentioning
confidence: 93%
“…Although further studies are needed, it appears that apoptotic mechanisms can also regulate axonal morphology. It will be interesting to investigate whether local activation of caspases can locally affect synapse structure and function from the presynaptic side [98,99].…”
Section: Long-term Depression In Neurodegenerationmentioning
confidence: 99%